2020
DOI: 10.1186/s12891-020-03403-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for bone loss in Southern Chinese with rheumatic diseases

Abstract: Backgroud: This study is to explore the prevalence of different stages of bone loss and the potential risk factors in rheumatic patients. Method: A cross-sectional study recruits 1398 rheumatic patients and 302 healthy subjects. Demographic data, blood, and bone mineral density (BMD) tests are collected. Risk factors for bone loss in rheumatic patients are analyzed by logistic regression. Results: (1) Rheumatic patients are consisted of 40.0% rheumatoid arthritis (RA), 14.7% systemic lupus erythematosus (SLE),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…To investigate the effect of each study on the pooled prevalence, we conducted a sensitivity analysis in which pooled prevalence are estimated omitting one study at a time. The highest pooled prevalence (28.1%, 95%CI 24.4–31.8%) was obtained by omitting the study of Innala et al 3 and the lowest pooled prevalence (27.0%, 95%CI 23.3–30.7%) was obtained by omitting the study of Hu et al 43 .…”
Section: Resultsmentioning
confidence: 86%
“…To investigate the effect of each study on the pooled prevalence, we conducted a sensitivity analysis in which pooled prevalence are estimated omitting one study at a time. The highest pooled prevalence (28.1%, 95%CI 24.4–31.8%) was obtained by omitting the study of Innala et al 3 and the lowest pooled prevalence (27.0%, 95%CI 23.3–30.7%) was obtained by omitting the study of Hu et al 43 .…”
Section: Resultsmentioning
confidence: 86%
“…Furthermore, the significant bone erosion, osteolytic defects, and the simultaneous induced expression of osteoclasts and inflammatory cytokines may result in the generation of FPFs [ 50 ]. Clinical studies also confirmed the close association between low Bone Mineral Density (BMD) and RA leading to increased bone loss and femoral frailty [ 51 , 52 ]. It was suggested that prevention of late FPFs could be accomplished by the intra-operative recognition of locations of cortical defects and osteolytic lesions and the prophylactically application of cortical grafts to reinforce cortical weakness and other stress risers [ 15 ].…”
Section: Discussionmentioning
confidence: 94%
“…Multiple studies have consistently shown an elevated prevalence of OP 7,33 and an increased susceptibility to fragility fractures 8 in individuals diagnosed with SLE. These observational studies align with our findings from the MR analysis, which established a causal effect of SLE on OP.…”
Section: Discussionmentioning
confidence: 99%